Entrepreneurial competence of primary school administrators in Thailand - Sirada Thongswat; Daoruwan Thawikan; Wallapa Arirat (Utilitas Mathematica, 2025)
The objectives of this research were as follows 1)To examine the consistency and alignment of the indicator model of entrepreneurial competencies among primary school administrators in Thailand with empirical data. 2) To investigate the core phenomena, conditions, strategies, and consequences associated with the development of entrepreneurial competencies among primary school administrators in Thailand.The sample consisted of 430 primary schools, selected using a multi-stage sampling method. Data were collected using a five-point Likert scale questionnaire. The data analysis involved basic statistical analysis, confirmatory factor analysis (CFA), and theoretical analysis of the core phenomena using the grounded theory research method. The study identified six key components of entrepreneurial competencies among primary school administrators in Thailand: 1.Innovative and creative thinking 2.Achievement motivation 3.Entrepreneurial social skills 4.Entrepreneurial management knowledge 5.Risk management for competitive opportunities 6.Entrepreneurial leadership. The model fit analysis indicated that the indicator model for entrepreneurial competencies among primary school administrators in Thailand demonstrated strong consistency with empirical data, with the following fit indices: χ² = 880.397, df = 813, χ²/df = 1.0829, P-Value = 0.0501, RMSEA = 0.014, SRMR = 0.018, CFI = 0.996, TLI = 0.995 The investigation of the core phenomena, conditions, strategies, and consequences further revealed that the core entrepreneurial competencies align with the six identified components.There were two causal conditions contributing to the emergence of entrepreneurial competencies.Four strategic approaches were identified to enhance these competencies. Additionally, there were two contextual conditions and two intervening conditions influencing the implementation of these strategies. The consequences of developing entrepreneurial competencies were observed across three areas: 1.The educational institutions 2.Administrators and personnel 3.The community.